2012
DOI: 10.1182/blood-2011-09-377598
|View full text |Cite
|
Sign up to set email alerts
|

Calcium blockers decrease the bortezomib resistance in mantle cell lymphoma via manipulation of tissue transglutaminase activities

Abstract: IntroductionMantle cell lymphoma (MCL) is an aggressive subtype of B-cell lymphoma that accounts for 5%-7% of cases of non-Hodgkin lymphoma. Despite good responses with first-line treatments for newly diagnosed, untreated MCL patients, 1-3 MCL patients often relapse and demonstrate highly refractory responses to common antilymphoma chemotherapy, which results in inevitable chemoresistance and poor clinical outcomes. [4][5][6][7] Bortezomib (Velcade), a reversible inhibitor of the 26S proteasome, first gained U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…The calcium is important in the epithelial cell differentiation (22). 4-HR inhibits TG-2 activity (14) and the activity of TG-2 is also calcium dependent (23). Therefore, the molecular mechanisms of the observed 4-HR-mediated effects may be partly dependent on calcium.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium is important in the epithelial cell differentiation (22). 4-HR inhibits TG-2 activity (14) and the activity of TG-2 is also calcium dependent (23). Therefore, the molecular mechanisms of the observed 4-HR-mediated effects may be partly dependent on calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Transglutaminases (TGases), also named protein-glutamine γ-glutamyltransferases, are enzymes belonging to the proteases class that catalyze post-translational modifications in many proteins by inter-or intramolecular cross-linking through acyl-transfer between y-carboxyamide groups of glutamine residues and ε-amino groups of lysines, or other primary amine, resulting in the formation of γ-glutamyl-ε-lysine peptide chain bridges Campos et al 2010;Hu et al 2011;Jung et al 2012;Li et al 2013;Lorand and Graham 2003). In the latter case, it is able to modify the protein substrate by "cationization" or by forming inter-or intramolecular bridges through polyamines of different length ).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA-binding activities of NF-kB components, TG2 enzymatic activity and IL-6 levels were determined by ELISA assays, as previously described (11,26). …”
Section: Methodsmentioning
confidence: 99%
“…It has multiple physiologic functions and is associated with cancer cell survival, metastatic behavior and drug resistance (59). TG2 has been proposed as a promising therapeutic target in the treatment of human cancers (10,11). Increasing evidence has demonstrated that TG2 is closely associated with constitutive nuclear factor-kappa B (NF-kB) expression in cancer cells (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation